1987
DOI: 10.1038/bjc.1987.136
|View full text |Cite
|
Sign up to set email alerts
|

Collagen IV staining pattern in bladder carcinomas: relationship to prognosis

Abstract: A prospective study of type IV collagen in urothelial tissues was undertaken using an immunoperoxidase method on 125 ethanol fixed specimens. In normal and non cancerous urothelium, the basement membrane was continuously stained and the same pattern was seen in the 27 superficial carcinomas. In the 48 invasive bladder carcinomas, we observed two patterns of staining for collagen IV: in the first one, the staining line was conserved or partially fragmented (28 tumours), while in the second one the staining line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 34 publications
(39 reference statements)
0
17
1
2
Order By: Relevance
“…This result also suggests that CB plays a role in tumour invasion and metastasis. In the past, many investigations have shown close relationship between the distribution of BM antigens, the incidence of distant metastasis and patient survival times (Foster et al 1984;Daher et al 1987). Nakajima (1991) has also showed that discontinuous pattern of CIV was associated with lymph node metastasis and with shorter survival times in lung adenocarcinoma.…”
Section: Resultsmentioning
confidence: 98%
“…This result also suggests that CB plays a role in tumour invasion and metastasis. In the past, many investigations have shown close relationship between the distribution of BM antigens, the incidence of distant metastasis and patient survival times (Foster et al 1984;Daher et al 1987). Nakajima (1991) has also showed that discontinuous pattern of CIV was associated with lymph node metastasis and with shorter survival times in lung adenocarcinoma.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, the integrity of the UBM was demonstrated using polyclonal and monoclonal antibodies to type IV collagen and/or laminin and was used to establish a relationship between superficial and invasive transitionalcell carcinomas, the latter often being associated with the loss of basement membrane staining [4,15,20]. Normally the UBM is continuous, with colocalization of type IV collagen and/or laminin occuring in normal and nonmalignant inflammation specimens [2,5], although an unspecified, indistinct staining pattern was found in 1 of 17 normals associated with inflammatory infiltrates in an earlier study [4]. The p53 protein, a cellular phosphoprotein thought to take part in the regulation of cell proliferation and a marker of transitional-cell carcinoma, was correlated with breaks in the UBM detected by laminin and type IV collagen staining and with the presence of the carcinoma [17].…”
Section: Discussionmentioning
confidence: 99%
“…9 We studied BM expression in bladder carcinomas to evaluate its use for the histopathologic identification of microinvasion. Furthermore, this study was performed to assess the usefulness of BM staining in comparison with grading, staging, and ploidy for the prediction of the biological behavior of bladder tumors.…”
Section: He Rapidly Increasing Knowledge In Molecularmentioning
confidence: 99%